2023
DOI: 10.1161/circulationaha.122.060573
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota–Derived Trimethylamine N-Oxide Contributes to Abdominal Aortic Aneurysm Through Inflammatory and Apoptotic Mechanisms

Abstract: Background: Large-scale human and mechanistic mouse studies indicate a strong relationship between the microbiome-dependent metabolite trimethylamine N-oxide (TMAO) and several cardiometabolic diseases. This study aims to investigate the role of TMAO in the pathogenesis of abdominal aortic aneurysm (AAA) and target its parent microbes as a potential pharmacological intervention. Methods: TMAO and choline metabolites were examined in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…In IL-17-treated VSMCs, NFKBID and NFKBIZ were upregulated ( Figure 9D ). As shown in Figures 14A, 14B , upregulated genes from innate immune genes, cytokines and chemokines, plasma membrane proteins, nuclear membrane proteins, nucleoli proteins, nucleoplasm proteins, TFs, oxidative stress cell death genes, necrotic cell death genes, pyroptosis cell death genes, efferocytosis genes, and fibrosis genes were downregulated in 5 master gene-deficient transcriptomic datasets including inflammatory TFs AHR –/– dataset ( 62 , 122 124 ), nuclear factor-kB (NF-kB) –/– with and without LPS stimulation dataset ( 125 127 ), superoxide-generating NADPH oxidase heavy chain subunit (NOX2) –/– dataset ( 23 , 37 , 128 , 129 ), endoplasmic reticulum (ER) stress ( 130 ) inducer) stimulation dataset, eukaryotic translation initiation factor 2 alpha kinase 3 (PRKR-like endoplasmic reticulum kinase, PERK –/– ( 7 , 131 )) and PERK –/– with tunicamycin (inhibitor of the UDP-N-acetylglucosamine-dolichol phosphate N-acetylglucosamine-1-phosphate transferase) dataset, trained immunity (innate immune memory)-promoting histone lysine methyltransferase SET7 –/– dataset ( 132 , 133 ) and were upregulated in antioxidant TF NRF2 –/– transcriptomic datasets ( 11 ), respectively. Our analysis showed that AhR and PERK deficiency had the most significant downregulation of innate immune genes, cytokines and chemokines, oxidative stress cell death genes, and nuclear stress genes ( Figure 14A ).…”
Section: Resultsmentioning
confidence: 99%
“…In IL-17-treated VSMCs, NFKBID and NFKBIZ were upregulated ( Figure 9D ). As shown in Figures 14A, 14B , upregulated genes from innate immune genes, cytokines and chemokines, plasma membrane proteins, nuclear membrane proteins, nucleoli proteins, nucleoplasm proteins, TFs, oxidative stress cell death genes, necrotic cell death genes, pyroptosis cell death genes, efferocytosis genes, and fibrosis genes were downregulated in 5 master gene-deficient transcriptomic datasets including inflammatory TFs AHR –/– dataset ( 62 , 122 124 ), nuclear factor-kB (NF-kB) –/– with and without LPS stimulation dataset ( 125 127 ), superoxide-generating NADPH oxidase heavy chain subunit (NOX2) –/– dataset ( 23 , 37 , 128 , 129 ), endoplasmic reticulum (ER) stress ( 130 ) inducer) stimulation dataset, eukaryotic translation initiation factor 2 alpha kinase 3 (PRKR-like endoplasmic reticulum kinase, PERK –/– ( 7 , 131 )) and PERK –/– with tunicamycin (inhibitor of the UDP-N-acetylglucosamine-dolichol phosphate N-acetylglucosamine-1-phosphate transferase) dataset, trained immunity (innate immune memory)-promoting histone lysine methyltransferase SET7 –/– dataset ( 132 , 133 ) and were upregulated in antioxidant TF NRF2 –/– transcriptomic datasets ( 11 ), respectively. Our analysis showed that AhR and PERK deficiency had the most significant downregulation of innate immune genes, cytokines and chemokines, oxidative stress cell death genes, and nuclear stress genes ( Figure 14A ).…”
Section: Resultsmentioning
confidence: 99%
“…We congratulate Benson et al 1 on the recent publication of their article in Circulation. The authors comprehensively reported that the disruption of the metaorganismal production of trimethylamine N-oxide (TMAO) by targeting either the gut microbiome or the liver enzyme flavin-containing monooxygenase 3 (FMO3) of the host organism decreases circulating TMAO and protects mice from abdominal aortic aneurysm development in 2 independent mouse models.…”
Section: Letter To the Editormentioning
confidence: 92%
“…In recent years, there has been a growing interest in the role of the microbiome in cardiovascular and cerebrovascular diseases [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The “microbiome” encompasses all microorganisms residing in or on various parts of the human body, which includes bacteria, fungi, and viruses (and all of their genes).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, attention has turned to the intestinal microbiome’s role in this process, with certain dietary components, such as carnitine from red meat and phosphatidylcholine from egg yolk, being metabolized by gut bacteria into trimethylamine, eventually converted in the liver into trimethylamine n-oxide (TMAO), which has been established as a risk factor for atherosclerosis [ 25 , 26 ]. For aortic aneurysms there is growing evidence about a potential role of the gut microbiome in formation and rupture [ 21 , 27 , 28 , 29 ]. For example, it was shown that patients with Campylobacter gracilis or Fusobacterium in their gut microbiome had a significantly higher incidence of aortic aneurysm-related events [ 27 ].…”
Section: Introductionmentioning
confidence: 99%